A prospective study of dairy product intake and the risk of hepatocellular carcinoma in U.S. men and women. Issue 5 (6th June 2019) - Yang, Wanshui; Sui, Jing; Ma, Yanan; Simon, Tracey G.; Chong, Dawn; Meyerhardt, Jeffrey A.; Willett, Walter C.; Giovannucci, Edward L.; Chan, Andrew T.; Zhang, Xuehong
Abstract : Although increasing dairy product intake has been associated with risk of several cancers, epidemiological studies on hepatocellular carcinoma are sparse and have yielded inconsistent results. We prospectively assessed the associations of dairy products (total, milk, butter, cheese and yogurt) and their major components (calcium, vitamin D, fats and protein) with the risk of hepatocellular carcinoma development among 51, 418 men and 93, 427 women in the Health Professionals Follow‐Up Study and the Nurses' Health Study. Diets were collected at baseline and updated every 4 years using validated food frequency questionnaires. Multivariable hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated using Cox proportional hazards regression model. During up to 32 years of follow‐up, a total of 164 hepatocellular carcinoma cases were documented. After adjustment for most known hepatocellular carcinoma risk factors, higher total dairy product intake was associated with an increased risk of hepatocellular carcinoma (highest vs . lowest tertile, HR = 1.85, 95% CI: 1.19–2.88; p trend = 0.009). For the same comparison, we observed significant positive associations of high‐fat dairy (HR = 1.81, 95% CI: 1.19–2.76; p trend = 0.008) and butter (HR = 1.58, 95% CI: 1.06–2.36; p trend = 0.04) with hepatocellular carcinoma risk. There was a nonsignificant inverse association between yogurt intake and hepatocellular carcinoma risk (HR = 0.72, 95% CI: 0.49–1.05; p trend = 0.26). Our data suggest that higher intake of high‐fat dairy foods was associated with higher, whereas higher yogurt consumption might be associated with lower risk of developing hepatocellular carcinoma among U.S. men and women. Abstract : What's new? In the US, liver cancer incidence has increased considerably in the last 30 years. Meanwhile, Americans are also eating more dairy products. These authors investigated the association between dairy consumption and risk of hepatocellular carcinoma (HCC). From participants in the Nurses' Health Study and the Health Professionals Follow‐Up Study, they collected diet information at baseline and again every 4 years. Although they considered individual components of dairy food, including calcium, fat, protein, and vitamin D, they found no association between HCC risk and any individual nutrient. They did find higher total dairy intake associated with higher risk of HCC, particularly for high‐fat products. Higher yogurt intake appears to be associated with a suggestive lower risk, which deserves further investigations.